Implementasi Materi Akhlak dalam Pembelajaran PAI untuk Menumbuhkan Karakter Toleransi di SDN 013 Balikpapan Kota - Ismail Yahya (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to examine the implementation of moral education content in Islamic Religious Education (PAI) learning in fostering students’ tolerance character at SDN 013 Balikpapan Kota. The research employs a qualitative descriptive approach by collecting data through observation, interviews, and documentation. The findings indicate that moral values, particularly tolerance, are systematically integrated into PAI learning through exemplary behavior, habituation, reflective dialogue, and contextual learning strategies. Teachers play a central role in internalizing tolerance values by demonstrating fair attitudes, encouraging respectful interactions, and facilitating inclusive classroom activities. The implementation of moral education is not limited to cognitive understanding but emphasizes affective and behavioral dimensions, enabling students to practice tolerance in daily interactions. The results also reveal that a supportive learning environment contributes significantly to the development of tolerant attitudes among students. However, strengthening consistency and collaboration between school and family remains necessary to enhance the sustainability of character formation. Overall, moral education within PAI learning functions as an effective medium for cultivating tolerance and social harmony among elementary school students.